Submarine Groundwater Discharge: Updates on Its Measurement Techniques, Geophysical Drivers, Magnitudes, and Effects - Taniguchi, Makoto; Dulai, Henrietta; Burnett, Kimberly M.; Santos, Isaac R.; Sugimoto, Ryo; Stieglitz, Thomas; Kim, Guebuem; Moosdorf, Nils; Burnett, William C. (Frontiers in Environmental Science, 2019)
The number of studies concerning Submarine Groundwater Discharge (SGD) grew quickly as we entered the 21st century. Many hydrological and oceanographic processes that drive and influence SGD were identified and characterized during this period. These processes included tidal effects on SGD, water and solute fluxes, biogeochemical transformations through the subterranean estuary, and material transport via SGD from land to sea. Here we compile and summarize the significant progress in SGD assessment methodologies, considering both the terrestrial and marine driving forces, and local as well as global evaluations of groundwater discharge with an emphasis on investigations published over the past decade. Our treatment presents the state-of-the-art progress of SGD studies from geophysical, geochemical, bio-ecological, economic, and cultural perspectives. We identify and summarize remaining research questions, make recommendations for future research directions, and discuss potential future challenges, including impacts of climate change on SGD and improved estimates of the global magnitude of SGD.